2002
DOI: 10.1002/bref.44
|View full text |Cite
|
Sign up to set email alerts
|

Structural breaks, diversification and international real estate markets — some new evidence

Abstract: This paper presents further evidence that real estate markets around the world are interrelated. Although it is shown that an initial examination may reveal that international real estate markets are not linked, once structural changes are accounted for, it becomes apparent that there are long-running relationships in securitised real estate returns across the world. This paper also shows that monetary changes in the USA -the world's leading economy -can impact on international real estate markets. This has ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…A drawback with the Gregory and Hansen approach, and which makes it unsuitable for the present analysis, is that the procedure cannot determine the rank of the system, and thereby the number of stochastic processes -the methodology is better suited to simply ascertaining the existence of co-integration in the presence of possible structural breaks. This was the avenue of research presented by Wilson and Zurbruegg (2002).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…A drawback with the Gregory and Hansen approach, and which makes it unsuitable for the present analysis, is that the procedure cannot determine the rank of the system, and thereby the number of stochastic processes -the methodology is better suited to simply ascertaining the existence of co-integration in the presence of possible structural breaks. This was the avenue of research presented by Wilson and Zurbruegg (2002).…”
Section: Methodsmentioning
confidence: 95%
“…For example, Gregory and Hansen (1996) have developed residual based tests along similar lines to the Zivot and Andrews (1992) unit root tests on univariate series. Analysis on the integration of property markets using this approach has been conducted by Wilson and Zurbruegg (2002) showing evidence that international real estate markets are co-integrated, once consideration is made for structural breaks. A drawback with the Gregory and Hansen approach, and which makes it unsuitable for the present analysis, is that the procedure cannot determine the rank of the system, and thereby the number of stochastic processes -the methodology is better suited to simply ascertaining the existence of co-integration in the presence of possible structural breaks.…”
Section: Methodsmentioning
confidence: 99%
“…They argued that diversification benefits through international real estate securities can only be achieved in the short run. Wilson and Zurbruegg (2002) tested for co-integration among the markets of UK, USA, Australia and Japan by applying the Gregory and Hansen co-integration test and found that the real estate markets were cointegrated after the structural breaks are taken into account.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The reason for this is that co-integration test results can be sensitive to the existence of structural breaks. Wilson and Zurbruegg's (2002) co-integration analysis shows that once possible structural breaks are taken into account, international real estate markets (Australia, Japan, UK and USA) have been interrelated since the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Given the results in Wilson and Zurbruegg (2002), it is interesting to investigate the influence of possible structural breaks on the diversification benefits of international real estate securities in the short-run under the mean-variance framework. It is likely that the diversification opportunities in the short run differ from in the long run.…”
Section: Introductionmentioning
confidence: 99%